QOLP-01. OUTCOME ASSESSMENT OF MULTIDISCIPLINARY BRAIN TUMOR BOARD MEETING RECOMMENDATIONS FOR BRAIN METASTASIS: IS THERE A GAP?. (9th November 2020) - Santos-Pinheiro, Fernando; Bovi, Joseph; Peltier, Wendy; Connelly, Jennifer; Mueller, Wade; Straza, Michael; Puckett, Lindsay; Crabb, Marianne; Leuck, Julianne; Zwagerman, Nathan; Thompson, Jonathan; Schultz, Christopher; et al.
Abstract: BACKGROUND: Brain metastasis (BM) is the most common form of brain cancer affecting 20-40% of cancer patients. Advancements in cancer therapy has prolonged survival but BM incidence has increased. BM management requires a multidisciplinary approach to individualize care via an ever-growing sum of surgical, radiation, and systemic therapy options. Consensus is achieved by multidisciplinary tumor board meeting (MTBm). Nevertheless, BM diagnosis predicts poor prognosis. Palliative Care (PC) is essential for proper BM management. Yet, formal PC assessment may not be available for MTBm. We evaluated whether MTBm consensus recommendations were followed. RESULTS: Our weekly MTBm discussed 157 BM cases during 2019 (median age: 64 years [range 28-91], male/female: 82/75). The most common primary diagnosis was lung (n=49, 31%), breast (n=24, 15%), melanoma (n=16, 10%). The majority was newly diagnosed BM (n=143, 91%). MTBm recommendations were divided into three not-mutually-exclusive categories: surveillance/workup (n=78, 50%), BM-directed treatment (n=101, 64%) and GOC discussion (n=7, 4%). MTBm recommendations were fully followed in 113 cases (72%), partially in 13(8%), and not followed in 25(16%). Of the 38 patients whose recommendations were partially/not followed, the main reason was transition to hospice/death (n=26, 68%). Of the 101 patients recommended treatment, 68% (n=68) fully followed it, yet 31% (n=21) of them died within 3 months; for those living longer than 3 months (n=47, 69%), median KPS at 3 months was 70 (range 30-90). Of the entire cohort (n=157), only 20 (13%) established consistent PC follow-up (>1 outpatient visit) and 69 cases (44%) transitioned to hospice/died within 6 months, 30 of which (43%) still completed surgery (n=6) or radiotherapy (n=24) within this period. CONCLUSION: Periodic assessment of MTBm recommendations is relevant for sensible BM management. Balancing treatment while focusing on QoL in a patient population with limited survival is challenging. PC assessment at MTBm could close this gap.